Difluprednate 0.05% versus Prednisolone Acetate Post-Phacoemulsification for Inflammation and Pain: An Efficacy and Safety Clinical Trial - Palacio-Pastrana C (Dove Medical Press, 2020)
Claudia Palacio-Pastrana,1 Eduardo Chávez-Mondragón,2 Abraham Soto-Gómez,3 Rubén Suárez-Velasco,4 Miguel Montes-Salcedo,5 Lourdes Fernández de Ortega,6 Linda Nasser-Nasser,7 Leopoldo Baiza-Durán,8 Oscar Olvera-Montaño,8 Patricia Muñoz-Villegas8 1Fundación Hospital Nuestra Señora de la Luz, IAP, CDMX, Mexico; 2Fundación de Asistencia Privada Conde de Valenciana, IAP, CDMX, Mexico; 3Catarata y Glaucoma de Occidente SA de CV, Guadalajara, Jalisco, Mexico; 4Private Office, Guadalajara, Jalisco, Mexico; 5Aris Vision Institute, Guadalajara, Jalisco, Mexico; 6Asociación Para Evitar la Ceguera en México, IAP, CDMX, Mexico; 7Visión Cirugía Ambulatoria, Monterrey, Nuevo Leon, Mexico; 8Medical Affairs, Laboratorios Sophia, SA de CV, Zapopan, Jalisco, MexicoCorrespondence: Patricia Muñoz-Villegas Tel +52 3001 4200 ext 1018Email patricia.munoz@sophia.com.mxBackground: The purpose of this study was to compare the efficacy and safety of difluprednate 0.05% (PRO-145) versus prednisolone acetate 1% (Prednefrin® SF), for management of postoperative inflammation and pain, after cataract surgery.Methods: This was a Phase III, multicenter, prospective, double-blind, clinical trial. Intent-to-treat population included 178 post-phacoemulsification patients that were assigned to receive either PRO-145, or prednisolone. One day after unilateral eye surgery, patients instilled a drop 4 times a day for 14 days (then tapering the dose downward for 14 days). The primary efficacy endpoints were anterior chamber (AC) cell grade and flare. Other parameters measured included: retinal central thickness (measured via OCT), conjunctival hyperemia, edema, pain and photophobia. Tolerability and safety were assessed through burning, itching, foreign body sensation, visual acuity (VA), intraocular pressure (IOP) and incidence of adverse events (AE).Results: A total of 171 subjects were randomized (1:1) and completed the study. Compared to day 1, there was a significant improvement in the AC cell count and flare in both groups by the final visit (80.2% vs 88.4%, p=1.000). Conjunctival hyperemia improved in a similar fashion (81.2% vs 79%, p=0.234) in both PRO-145 and prednisolone groups, without differences between them. This was also observed for edema (82.4% vs 82.5%, p=0.246), pain (15.3% vs 7%, p=0.497) and photophobia (16.4% vs 15.1%, p=0.246), respectively. There was no significant difference between treatments for any tolerability parameter studied. Finally, at the 4-week postoperative visit, there were no significant differences between treatments for VA, IOP and AE results (p-values; 0.095, 0.053 and 0.099, respectively).Conclusion: The results of this study suggest that PRO-145 is as effective and safe as prednisolone acetate in treating postoperative inflammation and pain in patients undergoing phacoemulsification. The study was registered at ClinicalTrials.gov as NCT03693989.Keywords: difluprednate, dose-reduction, cataract surgery, ophthalmic corticosteroids